2023
DOI: 10.11606/s1518-8787.2023057004782
|View full text |Cite
|
Sign up to set email alerts
|

Soroprevalência de anticorpos do vírus SARS-CoV-2 em escolares no município de São Paulo, 2020

Abstract: OBJETIVO: Estimar a soroprevalência de anticorpos do vírus SARS-CoV-2 em escolares de quatro a 14 anos de idade residentes no município de São Paulo, segundo variáveis clínicas, demográficas, epidemiológicas e sociais, durante o período de fechamento das escolas como medida de controle da covid-19. MÉTODOS: Realizou-se um inquérito sorológico em setembro de 2020 com amostra aleatória estratificada por tipo de rede de ensino (pública municipal, pública estadual e privada). Foi coletada amostra de sangue venoso … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…The clinical manifestations of individuals infected with SARS-CoV-2 are diverse. In the present study, the symptoms most frequently reported by participants in the screening questionnaire were headache, sore throat, runny nose, and fever, consistent with other studies ( 45 , 54 , 55 ). However, memory bias undoubtedly influenced the self-reported symptoms ( Figure 2 ), particularly those reported during the first testing period ( Figure 3 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The clinical manifestations of individuals infected with SARS-CoV-2 are diverse. In the present study, the symptoms most frequently reported by participants in the screening questionnaire were headache, sore throat, runny nose, and fever, consistent with other studies ( 45 , 54 , 55 ). However, memory bias undoubtedly influenced the self-reported symptoms ( Figure 2 ), particularly those reported during the first testing period ( Figure 3 ).…”
Section: Discussionsupporting
confidence: 92%
“…Prevention and protection measures, such as the use of masks and alcohol gel, frequent cleaning of contact surfaces, hand hygiene, and vaccination of individuals over 12 years of age (which started in January 2021) could have contributed to the low percentage of infected individuals in the population studied ( 43 , 44 ). In 2020, serological surveys were conducted in children and adults in the school community in other states of Brazil, specifically in the city of São Paulo, state of São Paulo ( 45 ), and in Fortaleza, state of Ceará ( 46 ). In São Paulo, a seroprevalence of 16.6% for SARS-CoV-2 antibodies was found in schoolchildren.…”
Section: Discussionmentioning
confidence: 99%